2013
DOI: 10.1002/adma.201301989
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐Impulse‐Induced Non‐Volatile Ferroelastic Switching of Ferromagnetic Resonance for Reconfigurable Magnetoelectric Microwave Devices

Abstract: A critical challenge in realizing magnetoelectrics based on reconfigurable microwave devices, which is the ability to switch between distinct ferromagnetic resonances (FMR) in a stable, reversible and energy efficient manner, has been addressed. In particular, a voltage-impulse-induced two-step ferroelastic switching pathway can be used to in situ manipulate the magnetic anisotropy and enable non-volatile FMR tuning in FeCoB/PMN-PT (011) multiferroic heterostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
190
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(193 citation statements)
references
References 46 publications
2
190
0
1
Order By: Relevance
“…2,8,9 In ferromagnetic films grown on piezoelectric substrates, the magnetic easy axis can be rotated and the ferromagnetic resonance frequency can be shifted by the electrically induced strain of the substrate. 6,10,11 In superconductor films, the superconducting transition temperature can be shifted by strain. 12,13 In strongly correlated materials, the electrical conductivity can be changed by several orders due to strain from the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…2,8,9 In ferromagnetic films grown on piezoelectric substrates, the magnetic easy axis can be rotated and the ferromagnetic resonance frequency can be shifted by the electrically induced strain of the substrate. 6,10,11 In superconductor films, the superconducting transition temperature can be shifted by strain. 12,13 In strongly correlated materials, the electrical conductivity can be changed by several orders due to strain from the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…This evolution of FE domains was also confirmed by PFM. 40,41 Therefore, the electric field dependence of polarization, as well as the strain, shows a hysteresis for the unipolar case. Figure 5(c) presents the strain measured along the x and y directions (defined in Fig.…”
mentioning
confidence: 96%
“…Further, analysis of RSM for (011) PMN-PT showed that up to 90% of the FE domain in the poled region contributed to this nonvolatile strain. 41 Taking advantage of this large anisotropic piezostrain of PMN-PT with (011) orientation, a giant electric-field-tuned magnetization has been demonstrated in CoFeB/PMN-PT multiferroic heterostructures and the maximum relative change of magnetization can be up to 83%. 23 Figure 6(a) presents the magnetic hysteresis (M-H) curves versus electric field measured along the [100] direction.…”
mentioning
confidence: 99%
“…Voltage control of magnetic anisotropy (VCMA) in multiferroics can be realized by strain transfer from a ferroelectric or piezoelectric layer to a ferromagnetic film, as the deformation of the ferromagnet changes the magnetoelastic anisotropy via inverse magnetostriction. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Recently, the influence of electric-field induced strain on magnetic anisotropy has been demonstrated in a variety of unpatterned and patterned multiferroic heterostructures including BaTiO 3 /FM, 7-10 PMN-PT/FM, [11][12][13][14][15][16][17][18] and PZN-PT/ FM [18][19][20][21][22][23] with FM ¼ Ni, 9,11,14 NiFe, 21 NiCo, 20 Co, 17 CoFe, 7,8 CoFeB, 15,16,23 Fe, 10 FeGaB, 19,22 and Fe 3 O 4 . 18 Electric-field tuning of ferromagnetic resonance (FMR) has als...…”
mentioning
confidence: 99%
“…In most reports, strong tuning of FMR in continuous ferromagnetic films on piezoelectric substrates is inferred from microwave cavity or vector network analyzer FMR measurements. 15,[18][19][20][21][22][23] In this letter, we experimentally study electric-field tuning of FMR in patterned Ni 80 Fe 20 microstrips on PMN-PT substrates using a spin diode (SD) measurement technique. Patterning of the ferromagnetic film is anticipated to introduce a magnetostatic shape anisotropy, which competes with the magnetoelastic anisotropy that is induced via transfer of piezoelectric strain.…”
mentioning
confidence: 99%